DIFFERENCES BETWEEN VIRTUAL AND VISUAL AESTHETIC PERCEPTION OF THE WORLD - Alikulova Hosila Akramovna; Mustafayev J.Sh. (Лучшие интеллектуальные исследования, 2024)
Abstract: Today, the science of aesthetics has a wide influence on the spiritual, educational, social and economic spheres of society. It is an expression of this. Studying the aesthetic taste and aesthetics of the society means improving the human spirituality and culture, developing the market economy, supply and demand, market economy and marketing, determining management tolerance, and simultaneously improving the quality of life.